Motivation Analysis of Students of IT Unggul Ad Durrah in Participating in Elementary School Swimming Lessons - Sary, Dewi Maya; Sirait, Rizky Purnama; Bangun, Arti Kurniaty; Anugrah, Tama; Angga, Syifa Ainun; Lumbantobing, Radja Sihombing Esrauli; Afarin, Fadya (CV. INSPIRETECH GLOBAL INSIGHT, 2025)
Purpose of the study: This study aimed to analyze the motivational factors influencing elementary school students' participation in swimming lessons at IT Unggul Ad Durrah Medan, Indonesia, and to identify key predictors of student engagement in aquatic activities. Materials and methods: A cross-sectional quantitative study was conducted with 156 elementary students (ages 7-12) from IT Unggul Ad Durrah. Data collection utilized the Sport Motivation Scale-28 (SMS-28) adapted for swimming contexts, demographic questionnaires, and participation records. Statistical analyses were performed using SPSS v27, including descriptive statistics, correlation analysis, and multiple regression. Results: Results revealed that intrinsic motivation (M = 4.23, SD = 0.87) was the strongest predictor of swimming participation, followed by identified regulation (M = 3.89, SD = 0.92). Significant gender differences were observed (p < 0.05), with female students showing higher levels of intrinsic motivation. Age was negatively correlated with external regulation (r = -0.34, p < 0.01). Conclusions: Intrinsic motivation significantly influences elementary students' participation in swimming lessons. Educational interventions should focus on fostering autonomous motivation while considering gender and age-related differences in motivational profiles.